2013
DOI: 10.4236/health.2013.512296
|View full text |Cite
|
Sign up to set email alerts
|

Influencing factors on time of breastfeeding initiation among a national representative sample of women in India

Abstract: Breastfeeding is seen as vital for mother and child and therefore is of great public health concern. Early initiation of breastfeeding within one hour of delivery is important as it reduces neonatal mortality. Increasing our understanding of barriers and reasons for not commencing early breastfeeding is important to improve strategies and conditions to overcome such barriers. Hence, the present study aimed to investigate factors influencing time of breastfeeding among women in India, focusing on health care ut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
23
0
2

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(31 citation statements)
references
References 40 publications
6
23
0
2
Order By: Relevance
“…The similar trends were seen in other studies. [10][11][12]14 The overall rate of initiation of breast feeding within one hour of birth is 15.8% in India and it has set a National goal to increase the rate by 50% and the practice of initiation of breast feeding colostrum was 75% within one hour of birth and similar higher rate of observation were noted in other parts in India since last 3 years. 1,3,14,15 There are beneficial and additional advantages of breast feeding other than nutritional requirement like affection, mental development of the baby, jaw development, emotional bonding between mother and baby, identification of early signs of illness, delay in growth and development, severity of illness of the baby noticed by lactating mother irrespective of her experience in breast feeding as observed by many studies.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The similar trends were seen in other studies. [10][11][12]14 The overall rate of initiation of breast feeding within one hour of birth is 15.8% in India and it has set a National goal to increase the rate by 50% and the practice of initiation of breast feeding colostrum was 75% within one hour of birth and similar higher rate of observation were noted in other parts in India since last 3 years. 1,3,14,15 There are beneficial and additional advantages of breast feeding other than nutritional requirement like affection, mental development of the baby, jaw development, emotional bonding between mother and baby, identification of early signs of illness, delay in growth and development, severity of illness of the baby noticed by lactating mother irrespective of her experience in breast feeding as observed by many studies.…”
Section: Discussionmentioning
confidence: 98%
“…1,3,14,15 There are beneficial and additional advantages of breast feeding other than nutritional requirement like affection, mental development of the baby, jaw development, emotional bonding between mother and baby, identification of early signs of illness, delay in growth and development, severity of illness of the baby noticed by lactating mother irrespective of her experience in breast feeding as observed by many studies. 1,3,4,12,16 Occupation and education level of the mother plays an important role in initiation of breast feeding. In this study it was observed that as education level is higher and working outside the house showed delay in initiation of breast feeding.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…25 Sandor M and Dalal K demonstrated that women with no education are almost 50% less likely to start breastfeeding compared to women with higher education. 26 Patel A et al revealed that higher maternal education (adjusted OR 2.00, 95% CI: 1.10-3.60) were associated with timely initiation of breast feeding. 22 The present study it was found that mother who were counselled during antenatal visits about need of breast feeding were more likely to associated with breast feeding within one hour.…”
Section: Discussionmentioning
confidence: 99%
“…Similar finding were noted by others authors in different parts of the country and world. 29,30 The strength of the study is that it provides useful baseline data for health care providers, public health specialists and policy makers. One potential limitation of this study could be the small localized population.…”
Section: Place Of Deliverymentioning
confidence: 99%